Breast cancer associated pathogenic variants among women 61 years and older with triple negative breast cancer - Chávarri-Guerra, YJ (2021)
Women with triple negative breast cancer (TNBC) have a high prevalence of BRCA1 mutations, and current clinical guidelines recommend genetic testing for patients with TNBC aged ≤60 years. However, studies supporting this recommendation have included few older women with TNBC. Methods: Genetic testing results from women aged >60 years with TNBC enrolled in the Clinical Cancer Genomics Community Research Network (CCGCRN) registry were included in this analysis. Prevalence of breast cancer-associated pathogenic variants (PVs) was compared across age groups. Results: We identified 151 women with TNBC aged >60 years (median 65 years; SD 5.3). Of these, 130 (86%) underwent genetic testing, and a breast cancer-associated PV was identified in 16 (12.3%; 95% CI 7-19): BRCA1 (n = 6), BRCA2 (n = 5), PALB2 (n = 2), ATM (n = 1) and RAD51C (n = 2). We found no differences in the proportion of patients with close blood relatives with breast (≤50 years) or ovarian cancer (any age) between PV carriers (37.5%) and non-carriers (34.2%) (p = 0.79). Among PV's carriers, the proportion of older women with a BRCA1 PV was lower when compared to younger women (37.5% vs 77.2%; p < 0.01). Conclusion: Breast cancer-associated PVs were found in an important proportion of women aged >60 years with TNBC undergoing genetic testing, including greater representation of BRCA2. These results suggest that older women with TNBC should be offered genetic testing, and that their exclusion based on chronologic age alone may not be appropriate.